Art 21 art in the twenty-first century. Seasons one and two ([Alexandria, Va.] Distributed by PBS Home Video, 2003)
Meet diverse contemporary artists through revealing profiles that take viewers behind the scenes into artist' studios, homes, and communities to provide an intimate view of their lives, work, sources of insipiration and creative processes.
DVD.
Directors of photography, Ken Kobland, Joel Shapiro, Bob Elfstrom, Dyanna Taylor. Closed-captioned for the hearing impaired.
Disc one (season one) : place, spiritually, identity, consumption -- disc two (season two) : stories -- loss and desire -- time -- humor.
Hosts: Steve Martin, Laurie Anderson, S. Epatha Merkerson, John McEnore.
Keywords: Art, American -- 21st century; Artist -- United States -- Biography